A Comparison of Mathematics Learning Approaches of Gifted and Non-Gifted Students - Ahsen Seda Bulut, Avni Yıldız, Serdal Baltacı (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
In this study, it was aimed to investigate the mathematics learning approaches of gifted students and successful students who were not diagnosed as gifted in terms of variables of giftedness, gender, grade level, parents’ profession and education level. Descriptive research model, which is one of the general survey models, was used in the study. For the 2018-2019 academic years, a total of 239 6th, 7th and 8th grade students, 84 of whom were gifted students and 155 of whom were non-gifted students, participated into the study. Data on gifted students were collected from the Science and Arts Center of a province in the Central Anatolia region, while data on non-gifted students were collected from a secondary school in the same province. Students' mathematics learning approaches were determined by using the “Scale of Mathematics Learning Approaches”. When the findings were examined, a significant differentiation was observed in favor of gifted students in the in-depth learning approach between gifted and non-gifted students. In addition, there is a significant difference in favor of female students in in-depth and strategic learning sub-dimensions among gifted students. When the mathematics learning approaches of gifted and non-gifted students were compared according to grade level, no significant difference was found in the 8th grade level average scores.